Small business management an entrepreneurial emphasis - Longenecker, Justin G. (Justin Gooderl) 1917-2005; Moore, Carlos W.; Petty, J. William 1942-; Palich, Leslie E (Thomson / South-Western, 2006)
Small Business Management, with its loyal following and great package, is far and away the market leading text in small business and has been for many years. It is a proven text, comprehensive in its approach, with the best fully integrated content, graphics, and resources devoted to business plan development. SBM has always been a step ahead of the competition (first to cover family businesses and first to integrate computer technology for small business) and continues to provide innovative coverage in each new edition. Increasingly adopted in hybrid courses that combine small business management and entrepreneurship and in standalone entrepreneurship courses, SBM shows aspiring business owners not only how to start a business but how to grow one.